PENGARUH PENGGUNAAN METODE STAD (STUDENT TEAMS ACHIEVEMENT DIVISION ) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Sapitri, Devi; Pasya, Rayi; Selamet, Selamet (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2016)
This study aims to determine the effect of using the STAD method (Student Teams Achievement Division) on student learning outcomes in subjects of Islamic Religion Education (PAI). After analyzing the data, the authors draw the following conclusions: 1) The use of the STAD method in PAI learning at Cimaragas 1 Junior High School in Ciamis Regency is in accordance with the components in the STAD method, namely: Class Presentation, Team, Quiz, Individual Progress Score, Team Recognition; 2) Student Learning Outcomes in PAI subjects are obtained using test instruments. The results of the pre test 1 control class were 69.00, the experimental class was 68.50. Pre test II: control class 74.33, experimental class 78.50. The results of test post 1 control class: 71.83 and 78.00 experimental class. The results of the post test II experimental class have a higher average, which is 85.66 than the 77.00 control class average. 3) There is the effect of using STAD method on student learning outcomes in PAI subjects with the percentage of N-gain is 9% for the control class, while 30% for the experimental class.